The optimal probe tone frequency for eSRT measurements at individual electrodes in children with cochlear implants. (1st December 2021) - Guo, Haowei; Lin, Biyu; Chen, Ting; Li, Yanping; Guo, Mingyong
Abstract: Background: Higher probe tone frequencies have been shown to increase the elicitation rates in electrically evoked stapedius reflex threshold (eSRT) measurements. Objectives: To determine the optimal probe tone frequency for contralateral eSRT measurements at individual electrodes in children with unilateral cochlear implants and to assess the relationship between eSRTs for this frequency and most comfortable levels (M-levels). Materials and methods: Contralateral eSRT measurements with three probe tone frequencies (226, 678, and 1000 Hz) at individual electrodes were performed on 26 paediatric Advanced Bionics cochlear implant recipients. Results: The elicitation rates of eSRTs for 226, 678, and 1000 Hz probe tones were 73.08% (57/78), 88.46% (69/78), and 88.46% (69/78), respectively. The average eSRT for the 1000 Hz probe tone was significantly lower than those for 226 and 678 Hz probe tones ( p <.001 and p =.009, respectively). ESRTs for the 1000 Hz probe tone and M-levels were significantly correlated at all tested electrodes (all p <.001). Conclusions and significance: The optimal probe tone frequency for contralateral eSRT measurement at individual electrodes in children with unilateral cochlear implants is 1000 Hz. ESRTs for the 1000 Hz probe tone are significantly correlated with M-levels and can be used to guide the M-levels setting in these children.